Heavy Metals, Escherichia coli and Salmonella spp. in Feeds, Reused Water, Wastewater and Manure from Swine Farms: A Case Report - Tulayakul, Phitsanu; Boonsoongnern, Alongkot; Kasemsuwan, Suwicha; Ratanavanichrojn, Nattavut; Netvichian, Ramnaree; Khaodhiar, Sutha (Agriculture and Natural Resources, 2012)
The levels of Escherichia coli and Salmonella spp., heavy metal contamination in feeds, wastewater and manure in swine farms containing more than 1,000 sows per farm were studied. There were high levels of contamination of E. coli in the dry swine manure and ﬁ nal wastewater, but low levels in the raw water and reused water. Salmonella had contaminated the raw water, reused water and ﬁ nal wastewater. E. coli was found in decreasing levels from high to low in the fattening feed, sow feed and nursery feed. Salmonella serogroup E was mainly found in raw water, while serogroups B and E were found in the swine manure. Signiﬁ cant levels of Cd and Pb were found in the swine manure, while high levels of Zn and Cu were found in the nursery and fattening feeds used on the swine farms. There were positive correlation coefﬁ cients among Zn, Cu and Pb levels, while Zn and Pb levels correlated with E. coli and total bacterial count levels in the ﬁ nal wastewater. This study revealed that animal feeds and water used on farms must be obtained from reliable sources and it is highly recommended that regularly monitoring and assessment is undertaken to ensure the health safety of pig production and pork quality and to address environmental concerns.